Hermeneutika Rabbaniy ala Hadis Qudsi Riwayat Huzaifah Bin Al-Yaman - Farihin, Hibbi (RIWAYAH, 2016)
Understanding the object is the purpose of every person. Understanding objects correctly is the hope of all searchers. In the world of philosophy, an attempt to seek and know the correct information included in the epistemology field. Models of Tafsīr/Hermeneutics and Ta’wīl method are the part of it. In general, the study of epistemology dwell on empirical and rational area. Each description yet incomprehensible and can not be proven in some sense, not worthy of being called a scientific description. In contrast to the above pattern, the Islamic epistemology make a place for the method of extracting information that is difficult touched by means of empirical and rational. M. Abeed al-Jabiri call it the ‘Irfāniy approach. This paper is about to expose one of the most appropriate methods and quick in understanding any kind, including The Qur’ān. This method is excerpted from a Qudsi Hadith told by H}użaifah bin al-Yamān. We call it the Rabbāniy method. This discussion is considered important because of the description of this method is became not listed in the methodology of understanding the object/text (Tafsīr/Hermeneutics), such as popular contemporary ‘Ulūm al-Qur’ān book today. It is feared, this science will eventually be ‘lost’ (not used), which in turn will impact on less precise understanding of researchers ahead on the object, which in the case of the example above is The Qur’ān.